Training of Trainers (ToT) on Clean Energy Options for Sustaining Agricultural Productivity Course Module - Ekepu, David; Nakayiwa, Florence Mayega; Majaliwa, Jackson Gilbert Mwanjalolo; Karume, Katcho (2025)
This training of trainers was focused on the clean energy options for sustaining agricultural productivity course module and was organised by RUFORUM on 11-14 February 2025. The overall the goal of the module is to impact micro-economies of rural communities through promotion of cost-effective clean energy options for enhanced agricultural value chains productivity. The virtual training was facilitated by Prof. Katcho Karume from Université Evangélique en Afrique, DRC and Prof. Majaliwa Mwanjalolo, RUFORUM Secretariat, Uganda. The training was conducted on zoom. During the four (4) days of the training, approximately 167 participants (Male=64% and Female=36%) attended the training. The participants came from 25 African countries including Kenya (24%), Uganda (20%), Ethiopia (14%), Nigeria (7%), Somalia (5%), Sudan (3%), South Africa (3%), Zimbabwe (2%), Cameroon (2%) and Ghana (2%). The training included five sessions: 1) power systems, renewable, clean, and their estimations; 2) clean energy options for agriculture value chains; 3) Conversion devices; 4) design to maintenance of on-farm clean energy system; and, 5) energy value chains economics. The training on renewable energy was generally well appreciated by participants. Additional areas of expertise suggested by participants such as green hydrogen, Artificial intelligence for climate modelling, biodiversity estimations and biofertilizers/biopesticides management can be explored for future RUFORUM trainings.